DESIGNING LISTENING MATERIAL SAMPLES BASED ON CONTEXTUAL TEACHING AND LEARNING APPROACH - Meo, Maria Prasedis Gembira; Bunau, Eusabinus; Rosnija, Eni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2013)
Abstrak: Penelitian ini bertujuan untuk menjawab permasalahan tentang materi pembelajaran listening yang diperlukan oleh siswa semester genap kelas XI SMA Negeri 5 Pontianak. Penelitian ini juga bertujuan untuk mengetahui materi pembelajaran listening yang sesuai dengan pendekatan pembelajaran kontekstual. Sumber informasi dalam penelitian ini adalah guru mata pelajaran bahasa inggris SMA Negeri 5 Pontianak dan buku teks yang dipakai. hasil wawancara dan analisis buku teks diketahui bahwa materi pembelajaran listening yang digunakan di sekolah tersebut tidak memenuhi seluruh aspek CTL. Oleh karena itu peneliti mendesain materi pembelajaran listening dengan pendekatan kontekstual. Aktivitas dan kegiatan dalam desain materi tersebut di sesuaikan dengan aspek pendekatan pembelajaran kontesktual. Kata kunci: desain materi, materi listening, pendekatan kontekstual Abstract: This research is aimed at answering the problem about the listening materials are needed by the second semester of eleventh grader of SMA Negeri 5 Pontianak. It was also about the materials are appropriate based on Contextual Teaching and Learning Approach. An interview conducted for the teacher and textbooks analysis based on the criterion Contextual Teaching and Learning Approach. The information sources for this research are the teacher of English in SMA Negeri 5 Pontianak and the textbooks which are used by the teacher. The result of the interview and the textbook analysis indicate that listening materials that are used by the teacher and the students, do not fulfill all aspects Contextual Teaching and Learning Approach. Hence, the researcher tried to design contextual listening materials in term of the text and the activities. The activities in the listening materials are designed based on all aspects of contextual teaching and learning approach. From the checklist, we conclude that listening material samples designed fulfill the approach of Contextual Teaching and Learning. Keyword: material designing, listening material, CTL